Fusarium Pallidoroseum (cooke) Sacc as a Biocontrol Agent for the Pea APhid Aphis Craccivora Koch - Sunitha V S (Department of Agricultural Entomology, College of Agriculture, 1997)
Detailed investigations were made on the entomogenous fungus Fusarium pallidoroseum (cooke) Sacc infecting cowpea aphid Aphis cracclvora koch. Field studies showed that spore suspension and wettable powder formulations were equally effective in controlling the pea aphid. 7 x 106 spores per ml suspension in water or a similar suspension of a wettable powder or quinalphos 0.05 per cent were found to be equally effective in controlling the aphids under field conditions. Spore suspension containing 3.5 x 106 spores